LEADERSHIP, MOTIVATION AND EMPLOYEE PERFORMANCE: THE ROLE OF EMPLOYEE ENGAGEMENT MEDIATION AT COVID-19 REFERRAL HOSPITALS IN MALANG CITY - Fathorrahman Fathorrahman; Mohammad Bukhori; Chandra Adi Wijaya (Jurnal Apresiasi Ekonomi, 2024)
Businesses need to endure the economic downturn because of the COVID-19 pandemic's effects. The organization must continue to operate through its personnel. When the corona virus is a threat, workers must continue to be motivated to put in more effort. In order to further boost employee engagement, the company's leadership was also put to the test in terms of their ability to influence the workforce. This kind of research uses a survey approach and is quantitative in nature. This study was carried out at the Malang Covid Referral Hospital. Using proportionate stratified random sampling, 100 respondents made up the research sample. The findings indicate that: 1) motivation directly affects employee engagement; 2) motivation directly affects employee performance; 3) leadership directly affects employee engagement; 4) leadership directly affects employee performance; 5) employee engagement directly affects employee performance; 6) motivation directly affects employee performance through employee engagement as an intervening variable; and 7) leadership directly affects employee performance through employee engagement as an intervening variable.Keywords: Employee Engagement, Leadership, Motivation, Performance.